2020
DOI: 10.11113/mjfas.v16n3.1491
|View full text |Cite
|
Sign up to set email alerts
|

Graphene from waste and bioprecursors synthesis method and its application: A review

Abstract: Recently, carbonaceous material such as porous carbon, carbon nanotubes (CNTs), graphene, graphene oxide (GO) and activated carbon has received tremendous attention from researchers. To date, the exploration of graphene is still in vast. Graphene has been applied in various applications which include polymer composites, energy storage, fuel cell and biomedical applications. This is due to its unique characteristics such as large surface area and high remarkable electronic, mechanical and thermal properties. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…140 Afterward, various natural carbonaceous sources, such as plants, wood parts, biomass waste, fruits, vegetables, biopolymers and insect parts, have been explored in research literature for graphene derivatives production by biomass carbonization. 124,141 Figure 11 demonstrates examples of the exploited biomass for 2D GDs synthesis through pyrolysis in inert atmosphere. 124 The principal of graphene synthesis from biomass carbonization is based on the pyrolysis of biomass upon thermal treatment at high temperature ∼ 1000°C under an inert atmosphere.…”
Section: Bottom-up Synthesis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…140 Afterward, various natural carbonaceous sources, such as plants, wood parts, biomass waste, fruits, vegetables, biopolymers and insect parts, have been explored in research literature for graphene derivatives production by biomass carbonization. 124,141 Figure 11 demonstrates examples of the exploited biomass for 2D GDs synthesis through pyrolysis in inert atmosphere. 124 The principal of graphene synthesis from biomass carbonization is based on the pyrolysis of biomass upon thermal treatment at high temperature ∼ 1000°C under an inert atmosphere.…”
Section: Bottom-up Synthesis Techniquesmentioning
confidence: 99%
“…19 Thus, a recent study on the mechanical properties of ceramic composites based on alumina and zirconia with carbon allotropes, reported that graphene derivatives significantly enhance the fracture toughness, low-temperature wear resistance, creep behavior and superplasticity at high temperatures of ceramic materials. 141 Also, graphene largely modifies the electronic behavior of ceramic materials. For example, Pernia et al 161 have developed 3 mol% yttria tetragonal zirconia polycrystalline (3YTZP) ceramic composites with graphene nanoplatelets (GNPs), via Ex-situ solution mixing using ultrasound agitation.…”
Section: D Graphene Derivatives/inorganic Materials Compositesmentioning
confidence: 99%
“…In some variations, microwaveassisted hydrothermal method is also adopted, where microwave heating facilitates faster reaction to form GCDs with uniform size distribution [102][103][104][105][106]. Apart from GCD, graphene sheets are obtained from glucose via carbonization and calcination in the presence of some activating agents (like FeCl 3 etc) [107,108]. In another interesting process, chemical blowing techniques are utilized to blow molten sugar (or glucose) to prepare graphene.…”
Section: Green-chemical Reduction Of Graphene Oxidementioning
confidence: 99%
“…This not only conserves energy but also preserves material integrity, facilitating the rapid metamorphosis of soft carbon into graphite endowed with comparable properties to conventional graphite . Following this, both chemical exfoliation and thermal reduction stand out as preferred approaches, given their extensive exploration as feasible avenues for producing graphene-based materials. , The methodology combining Hummer’s method with thermal annealing has garnered substantial attention due to its scalability, operational simplicity, moderate reaction conditions, and cost-effectiveness …”
Section: Introductionmentioning
confidence: 99%